THE EXISTANCE OF SURAU ON MADURESE'S SETTLEMENT PATTERN AND SOCIAL BEHAVIOR (International Conference on Social and Islamic Studies, 2021)
This research aimed at knowing the existence of Surau in residential locations (traditional and modern) of Madurese people. In which every Taneyan has a Surau or Langgar in the western part of their front yard.This research was descriptive research. The data obtained were analyzed using the data analysis method by Miles and Huberman that employed data reduction, data presentation, and conclusions. The results showed that the presence of Surau in every Madurese residence was a must. So that in every Taneyan (yard) it would be found a Surau building. Surau was proof of the Madurese people’s obedience in which the majority of Madurese people are Muslims. Besides being used to worship God, Surau was also used as a place to  receive guests to protect the honor of family members from in appropriate attitudes. Because, according to the Madurese people, self-respect was an important point in their life. However, during the times, the use of Surau had become even more widespread, it was used to conduct educational activities such as teaching and learning about Islam, general knowledge, social interactions, and attitudes. The position of the Surau would always be at the corner (front) of the house according to the settlement pattern of the Madurese people, namely Taneyan  Lanjeng. The placement of the Surau was also at the corner of the west side of the house following the direction of the Muslim Qibla (Ka’ba) to carry out prayers. In the traditional settlement of the Madurese people, Surau building had simple architecture. However, currently, the design of Surau had changed both in terms of building architecture and ornaments. This was due to people's income, changes in social status, and the diversity of community jobs. Based on about Surau of settlement pattern Madurese people which confirms existence of the surau,then it will reflection about social behavior in society. So that it will be confirm about social behavior. There are three approaches, social behavior by conditioning or habits, social behavior by insight or understanding, and social behavior by models or examples.